Extracellular CIRP promotes Kupffer cell inflammatory polarization in sepsis - Shimizu, Junji; Murao, Atsushi; Lee, Yongchan; Aziz, Monowar; Wang, Ping (Frontiers in Immunology, 2024)
Sepsis is a life-threatening inflammatory condition caused by dysregulated host responses to infection. Extracellular cold-inducible RNA-binding protein (eCIRP) is a recently discovered damage-associated molecular pattern that causes inflammation and organ injury in sepsis. Kupffer cells can be activated and polarized to the inflammatory M1 phenotype, contributing to tissue damage by producing proinflammatory mediators. We hypothesized that eCIRP promotes Kupffer cell M1 polarization in sepsis.We stimulated Kupffer cells isolated from wild-type (WT) and TLR4 -/-mice with recombinant mouse (rm) CIRP (i.e., eCIRP) and assessed supernatant IL-6 and TNFα levels by ELISA. The mRNA expression of iNOS and CD206 for M1 and M2 markers, respectively, was assessed by qPCR. We induced sepsis in WT and CIRP -/-mice by cecal ligation and puncture (CLP) and assessed iNOS and CD206 expression in Kupffer cells by flow cytometry.Results: eCIRP dose-and time-dependently increased IL-6 and TNFα release from WT Kupffer cells. In TLR4 -/-Kupffer cells, their increase after eCIRP stimulation was prevented. eCIRP significantly increased iNOS gene expression, while it did not alter CD206 expression in WT Kupffer cells. In TLR4 -/-Kupffer cells, however, iNOS expression was significantly decreased compared with WT Kupffer cells after eCIRP stimulation. iNOS expression in Kupffer cells was significantly increased at 20 h after CLP in WT mice. In contrast, Kupffer cell iNOS expression in CIRP -/-mice was significantly decreased compared with WT mice after CLP. CD206 expression in Kupffer cells was not different across all groups. Kupffer cell M1/M2 ratio was significantly increased in WT septic mice, while it was significantly decreased in CIRP -/-mice compared to WT mice after CLP.Our data have clearly shown that eCIRP induces Kupffer cell M1 polarization via TLR4 pathway in sepsis, resulting in overproduction of inflammatory cytokines. eCIRP could be a promising therapeutic target to attenuate inflammation by preventing Kupffer cell M1 polarization in sepsis.